Pemberdayaan Masyarakat Melalui Budidaya Tanaman Hias di Kelurahan Banyorang Kecamatan Tompobulu Kabupaten Bantaeng - Nurul Fadilah; Muliaty Amin; Hasaruddin (Jurnal Berita Sosial, 2023)
This research aims to describe how the empowerment process of ornamental plant cultivation in Banyorang Village, Tompobulu District, Bantaeng Regency and how economic values and social values are in empowering ornamental plants for family life. In the explanation of this journal, the type of research is a qualitative research that uses descriptive analysis methods while the data analysis used is data reduction, data presentation, and drawing conclusions. The results of this study show that: Forms of community empowerment through ornamental plant cultivation in Banyorang Village, Tompobulu District, Bantaeng Regency, including community hobby background, community enthusiasm for PKK programs on cultivation, community actions, for sustainable cultivation. Economic value and social value in empowering ornamental plants for family life, including: economic value, social value.